Nice is Different than Good: Longitudinal Communicative Effects of Realistic and Cartoon Avatars in Real Mixed Reality Work Meetings - Dobre, Georgiana Cristina; Wilczkowiak (SHE/HER), Marta; Gillies, Marco; Pan, Xueni; Rintel, Sean (CHI 2022, 2022)
We report a within-subjects study of the effect of realistic and cartoon avatars on communication, task satisfaction, and perceived sense of presence in mixed reality meetings. For 2 − 3 weeks, six groups of co-workers (14 people) held a recurring real work meeting using Microsoft HoloLens2 devices. Each person embodied a personalised full-body avatar with a realistic face and another with a cartoon face. Half the groups started in the realistic condition and the other half started in the cartoon condition; all groups switched conditions half-way. Initial results show that, overall, participants found the realistic avatars’ nonverbal behaviour more appropriate for the interaction and more useful for understanding their colleagues compared to the cartoon one. Regarding the results over time, we identify different insights for cartoon and realistic avatars based on the type of avatar was embodied first. We discuss the implications of these results for mixed and virtual reality meetings.